2019
DOI: 10.1186/s40497-019-0158-2
|View full text |Cite
|
Sign up to set email alerts
|

Profitability and constraints to urban exotic vegetable production systems in the Kumasi metropolis of Ghana: a recipe for job creation

Abstract: Some vegetable producers perceive their venture to be unprofitable owing to cheating at the farm gate. This study sought to determine profitability of production of exotic vegetables which are not native of Ghana. The study used data collected from 80 urban exotic vegetable farmers. Descriptive statistics, gross margin analysis, multiple linear regression, and the Garrett ranking scale were the methods of analysis. The most profitable system from the results of the net margin ratio was the production of lettuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The high prices accruing to agricultural inputs (whereas capital available for the production process by farmers is quite small) constitutes a serious barrier to increasing production. This is in line with the findings of Manu et al (2019) and Wongnaa et al (2019) that high cost of input severely affected vegetable farmers in their production activities.…”
Section: Constraints Faced In Vegetable Productionsupporting
confidence: 92%
See 1 more Smart Citation
“…The high prices accruing to agricultural inputs (whereas capital available for the production process by farmers is quite small) constitutes a serious barrier to increasing production. This is in line with the findings of Manu et al (2019) and Wongnaa et al (2019) that high cost of input severely affected vegetable farmers in their production activities.…”
Section: Constraints Faced In Vegetable Productionsupporting
confidence: 92%
“…This resulted in poor pricing and a reduction in their income. Wongnaa et al (2019) reported a similar finding that postharvest loss severely affected exotic vegetable production.…”
Section: Constraints Faced In Vegetable Productionmentioning
confidence: 60%
“…Our results is consistent with Adams et al (2020) and Haruna et al (2012), who found profitability ratios of less than 1 for tomato producers in Ghana and Nigeria, respectively. Darko-Koomson et al (2020) and Wongnaa et al (2019) reported higher profitability associated with cassava and vegetable production in Ghana, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Overall, the operating ratio of 0.97 suggests tomato farming as a profitable enterprise to embark on. Not just tomato production; it also depicts profitability of Ghana's agricultural production in general (Wongnaa and Awunyo-Vitor, 2013; Wongnaa et al , 2019a, 2019b; Darko-Koomson et al , 2020).…”
Section: Resultsmentioning
confidence: 99%